Neurocognitive and symptom profiles of concussed and nonconcussed provincial rugby players over one season - Clark, Susan Beverley (Rhodes University, Faculty of Humanities, Department of Psychology, 2010)
Neurocognitive and symptom profiles of concussed and nonconcussed adult provincial rugby union players were investigated over one rugby season, including early season (baseline), intermittent postconcussion, and end of season testing. In a non-equivalent quasi-experimental design, nonconcussed (n = 54) and concussed (n = 17) rugby groups were compared with demographically equivalent noncontact sport controls (n = 37, and n = 17, respectively). Measures included the ImPACT cognitive and symptom composites, and the WMS-III Visual Reproduction and Verbal Paired Associates subtests. The independent and dependent comparative analyses in respect of both nonconcussed and concussed groups, provided cross-validation of poorer acute and/or chronic neuropsychological outcomes for the rugby groups on the ImPACT Reaction Time, Visual Motor Speed, Impulse Control and Symptom composites, and the WMS-III Verbal Paired Associates. The finding of significantly poorer scores on Verbal Paired Associates up to 24 days post concussion for the rugby players versus controls, was longer than the 7 "“ 10 day recovery period frequently cited in the literature. The overall implication of the study is that even in a group with high cognitive reserve such as these provincial level athletes, there may be prolonged acute recovery, as well as permanent deleterious neuropsychological consequences of cumulative concussive injury in association with a sport such as rugby. Accordingly, the move towards careful individualised postconcussion monitoring of neurocognitive functioning is endorsed, including early identification of any significant permanent reductions in cognitive reserve. Sensitivity of the ImPACT test might be enhanced via inclusion of a verbal associate learning task.
Keywords: Rugby football injuries; Brain -- Concussion -- Complications; Head -- Wounds and injuries -- Complications; Sports injuries -- Psychological aspects; Brain damage; Neuropsychological tests; Rugby Union football players